Effects of Cucumber Mosaic Virus on Cellular Components, Host Physiology and Yield of Chilli (Plant Tissue Culture and Biotechnology, 2019)
Alteration of cellular components and host physiology due to five biotypes of Cucumber mosaic virus (CMV) were investigated to know the effects on ultimate growth and yield of chilli. Severe reduction of cellular components like chlorophyll-a (59.31%), chlorophyll-b (68.40%), total chlorophyll (63.20%) and β-carotene (51.14%) were observed in plant infected by mosaic and stunting (MoS) as compared to healthy plant. The ratio of RNA to DNA was increased in the infected leaves. The reduction of photosynthesis rate was found 6.32 to 17.10% in CMV infected plants as compared to healthy plants. Stomatal conductance and inter cellular CO2 was found lower in CMV infected plats. Considerable yield reduction (28.80 to 78.11%.) was found infected with five symptomatic isolate of CMV. The present findings indicate that multiplication of virus particles in the infected cells alter the biochemical compounds of cells that disrupt the physiological process which affect the growth and yield of chilli.